(untitled) (Epidemiology, Biostatistics, and Public Health, 2022)
Background: From November 2015 to January 2016, the routine air monitoring showed a peak of air pollution (in particular of PM10) that caused alarm in many Italian cities and was widely reported by mass media. After some weeks from this alarm, we tried to evaluate the citizen awareness and interest towards air pollution together with their positive behaviors, using different information sources. Methods: From September 2015 to March 2016, in parallel with the number of exceedances of the PM10 in Italy we evaluated the press coverage, the average monthly searches on Google and the interest on Twitter. Moreover, a qualitative content analysis on daily newspapers was conducted and a self-compiled questionnaire on the attitudes and behaviors about environmental issues and their determinants was administered to 598 parents involved in the project MAPEC_LIFE (LIFE12 ENV/IT/00614). Results: The media coverage of the theme of air pollution was very high from the end of 2015 to the beginning of 2016, as well as internet searches and twitter messages. Our qualitative analysis highlighted that only a small portion of articles included information about positive behaviors and environmental awareness. Despite the high media coverage and the satisfactory self-perceived knowledge, the majority of respondents judged negatively the received information (as untrue and incomplete) and declared a limited adoption of pro-environmental behaviors. Conclusion: The parallel study of mass media information and people’s attitudes and behaviors seem to indicate that the high media coverage was not followed by a very high motivation towards pro-environmental behaviors.